Effectiveness of immunosuppressant use for the treatment of immune checkpoint inhibitor-induced liver injury: A systematic review and meta-analysis - Chen, Kefan; He, Junhao; Xu, Jing; Chen, Jie (Frontiers in Oncology, 2023)
Background Immune-mediated liver injury caused by checkpoint inhibitors (ILICI) is a challenging clinical management issue. Although immunosuppressants are widely used to manage ILICI, no large-scale studies have proved definitive evidence for the most effective form of patient management. Aim Analysis of the effectiveness of immunosuppression for immune-related liver injury. Methods We performed a systematic review and meta-analysis of the clinical outcomes of immunosuppressive treatment of ILICI patients. A literature search of PubMed, Ovid, and Cochrane Library was completed for dates from 2000 to January 1, 2022. The primary outcome was the response rate to immunosuppressive therapy for ILICI, with subgroup analysis based on the type of cancer, immune checkpoint inhibitor regimen, and severity of liver injury. The secondary outcome was the median time to recovery from ILICI with immunosuppressive therapy. Results A total of 30 studies that included 1120 patients were collected. The pooled ILICI response rate was 79% (95% CI 0.73-0.84) for treatment with corticosteroids and 93% (95% CI 0.79-1.0) for treatment with mycophenolate mofetil. For ILICI treated with corticosteroids, the median recovery time was 47.59 (95% CI 39.79-55.40) days compared to 37.74 (95% CI 31.12-44.35) days for all forms of immunosuppression. Conclusion Findings support the effectiveness of corticosteroids and mycophenolate mofetil for the treatment of ILICI. The identified median time to recovery is a beneficial guide for patients and physicians, allowing for realistic expectations and appropriate treatment management. Future prospective randomized controlled trials are required to define a standardized management approach to immunosuppressive therapy of ILICI.